Nutrition: A Primary Therapy in Pediatric Acute Respiratory Distress Syndrome - Wilson, Bryan; Typpo, Katri (Frontiers in Pediatrics, 2016)
Appropriate nutrition is an essential component of intensive care management of children with Acute Respiratory Distress Syndrome (ARDS) and is linked to patient outcomes. One out of every two children in the PICU will develop malnutrition or have worsening of baseline malnutrition, and present with specific micronutrient deficiencies. Early and adequate enteral nutrition (EN) is associated with improved 60-day survival after pediatric critical illness and yet, despite early EN guidelines, critically ill children receive on average only 55% of goal calories by PICU day 10. Inadequate delivery of EN is due to perceived feeding intolerance, reluctance to enterally feed children with hemodynamic instability, and fluid restriction. Underlying each of these factors is large practice variation between providers and across institutions for initiation, advancement and maintenance of EN. Strategies to improve early initiation, advancement, and to maintain delivery of EN are needed to improve morbidity and mortality from pediatric ARDS. Both over and underfeeding prolongs duration of mechanical ventilation in children and worsens other organ function such that precise calorie goals are needed. The gut is thought to act as a ‘motor’ of organ dysfunction and emerging data regarding the role of intestinal barrier functions and the intestinal microbiome on organ dysfunction and outcomes of critical illness present exciting opportunities to improve patient outcomes. Nutrition should be considered a primary rather than supportive therapy for pediatric ARDS. Precise nutritional therapies, which are titrated and targeted to preservation of intestinal barrier function, prevention of intestinal dysbiosis, preservation of lean body mass, and blunting of the systemic inflammatory response, offer great potential for improving outcomes of pediatric ARDS. In this review we examine the current evidence regarding dose, route, and timing of nutrition, current recommendations for provision of nutrition to children with ARDS, and the current literature for immune modulating diets for pediatric ARDS. We will examine emerging data regarding the role of the intestinal microbiome in modulating the response to critical illness.